(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Routing is one of the most crucial problems that significantly affects the performance ofmultihop networks, such as the Internet and Mobile Ad-hoc Networks.This study investigates the viabilityof adopting shortest path routing in wireless sensor networks. An ideal routing algorithm shouldstruggle to locate the best route for data that must be transferred in a precise amount of time.In thispaper Route Discovery, Traffic Aware RBF-Neural network Approximation, and Traffic Aware RouteSelection are three methods are proposed for AODV advancement technique for route selection andpacket forwarding